Effect of calcium hydroxide pastes and vehicles on root canal dentin microhardness - María G Pacios; Gastón Lagarrigue; Nicolás Nieva; María E López (Wolters Kluwer Medknow Publications, 2014)
Background: Calcium hydroxide pastes used in the endodontic therapy may produce changes in the physical properties of the dentin. Objective: The purpose of this study was to evaluate the effect of calcium hydroxide pastes and their vehicles on microhardness of root canal dentin. Materials and Methods: Sixty maxillary anterior teeth were used. The crowns of the teeth were removed at the cemento-enamel junction. Canals were instrumented, horizontally sectioned into 2 segments, embedded in acrylic resin, and polished. A total of 120 specimens were randomly divided into 12 groups. Specimens stayed in contact with the vehicles or the pastes prepared with the calcium hydroxide powder and the same vehicles. The vehicles are: Distilled water, chlorhexidine, carticaine in the anesthetic solution, propylene glycol, monochlorophenol and monochlorophenol - propylene glycol. The references Vickers microhardness were obtained prior the application of the medicaments. Samples were then exposed to the medicaments for 3, 7, and 14 days, and microhardness measured again. The results were statistically analyzed by one-way ANOVA, Tukey test, and regression. Results: All vehicles and pastes, except distilled water, significantly decreased the microhardness of the root dentin; however, calcium hydroxide + camphorated monochlorophenol - propylene glycol and camphorated monochlorophenol - propylene glycol showed the highest decrease. Conclusion: Vehicles contribute to calcium hydroxide reduction of root canal dentin microhardness as constituent of endodontic pastes.